2009
DOI: 10.1590/s1519-69842009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among South Brazilian accessions of Lippia alba Mill. (Verbenaceae) detected by ISSR and RAPD markers

Abstract: Twenty-seven accessions of Lippia alba Mill. collected in Rio Grande do Sul state, Brazil, were analysed by ISSR and RAPD markers to evaluate their genetic variability and relationships. Six ISSR primers and four RAPD primers generated 120 amplified fragments, most of which were polymorphics. The overall genetic variability among accessions was very high when compared with other plant species. The hierarchical analysis of molecular data (UPGMA) showed low relationship between accessions, and no grouping betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
4
23
1
3
Order By: Relevance
“…Observed high level of genetic variability in this species, which were also detected by Manica-Cattani et al (2009) that studied 27 genotypes of L. alba through molecular markers : Harvest × progeny Interaction; σ P 2 : progeny variance; σ E 2 : Environmental variance = error b of ANOVA; CV G% : Genetic coeffient variation among half-sib progenies; CV E% : Environmental variation coefficient; h r 2 (%): narrow-sense heritability; b: Relationship CV G% / CV E% ; G S : absolute gain under 30% of selection intensity; G S% : selection gain related to the mean; LDM: dry mass of leaves per plant; TDM: total dry mass per plant; LY: leaves yield; EOY: oil yield; OP: oil production per plant. To make correlation estimates more robust, all progenies for all three harvests were taken into account in the ANOVAs (Table 4).…”
Section: Resultssupporting
confidence: 62%
“…Observed high level of genetic variability in this species, which were also detected by Manica-Cattani et al (2009) that studied 27 genotypes of L. alba through molecular markers : Harvest × progeny Interaction; σ P 2 : progeny variance; σ E 2 : Environmental variance = error b of ANOVA; CV G% : Genetic coeffient variation among half-sib progenies; CV E% : Environmental variation coefficient; h r 2 (%): narrow-sense heritability; b: Relationship CV G% / CV E% ; G S : absolute gain under 30% of selection intensity; G S% : selection gain related to the mean; LDM: dry mass of leaves per plant; TDM: total dry mass per plant; LY: leaves yield; EOY: oil yield; OP: oil production per plant. To make correlation estimates more robust, all progenies for all three harvests were taken into account in the ANOVAs (Table 4).…”
Section: Resultssupporting
confidence: 62%
“…Many species of Verbenacea are used as important folk remedies for the treatment of several human health disorders, like some kinds of cancer and hypertension (Ghisalberti, 2000;Manica-Cattani et al, 2009). Due to the medicinal importance or toxic effects of several species of Verbenaceae, efforts have been made to develop markers that allow distinguishing among species.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that the 2 molecular markers investigated in this study, namely ISSR and RAPD, efficiently identified and discriminated the Achillea species, allowing the characterization of all the accessions under study. The efficiency of these molecular markers for genotype identification in other aromatic and medicinal plants has been reported (Mattioni et al, 2002;Torres et al, 2003;Fracaro et al, 2005;Manica-Cattani et al, 2009).…”
Section: Inter-and Intra-specific Genetic Diversity Of Yarrow Speciesmentioning
confidence: 99%
“…It has been shown that different markers might reveal different kinds of variation (Powell et al, 1996). RAPD markers (Williams et al, 1990) and ISSR markers (Zietkiewicz et al, 1994) have been used with success to identify and determine relationships at the species, population, and cultivar levels in many plant species, including several aromatic and medicinal plants (Mattioni et al, 2002;Nan et al, 2003;Fracaro et al, 2005;Manica-Cattani et al, 2009;de Lima et al, 2011). However, there are limited reports on the genetic relationships of Achillea species.…”
Section: Introductionmentioning
confidence: 99%